Objektivnost merinih instrumenata situaciono-motoricke koordinacije u sportskoj gimnastici - Velickovic, S.; Petkovic, E. (Facta Universitatis: Series Physical Education and Sport, 2005)
On a sample of 112 boys and girls who had previously been selected for gymnastics from six of the elementary schools of Niš, the metric characteristics of 19 situational-motor coordination tests which are known to date and which have been used in the selection process in gymnastics in eight countries in Europe and the former Yugoslav republics have been determined. The authors have classified the aforementioned measuring instruments into five hypothetical areas of coordination including: The performance speed of complex motor tasks (4); Agility (3); Rhythm coordination (4); Precise performance of complex motor tasks (6); The precise management of hand motions in space (2). This paper presents the results of the objectivity of measuring instruments by calculating Pearson's correlation coefficient and by implementing Hotelling's canonical-correlational analysis for each of the tests for the purpose of evaluating the objectivity of the analyzed composite tests. Two sets of variables, between which a canonical correlation was found to exist and therefore the objectivity of the composite test represented the course three measurings which were noted on the part of two measurers in an actual test on involving the same sample of examinees. Bearing in mind that the value of the first pair of canonical factors best explains the connection between the two systems of variables, the first canonical equation root was used as the indicator for the objectivity of the given composite test. The aforementioned results indicate that 18 out of the 19 measuring instruments for the evaluation of situational-motor coordination in gymnastics have significant values when it comes to objectivity and can be recommended for practical use. Only one of the tests for the evaluation of the ability to precisely perform complex motor tasks - the Standing jump accompanied by asymmetrical motions of the extremities (SJSE) was classified among the group of measuring instruments of unacceptable objectivity and requires additional restandardization of the measurement procedure.